Comparison of urine cytology and fluorescence in situ hybridization in upper urothelial tract samples. Issue 6 (6th March 2014) - Reynolds, Jordan P.; Voss, Jesse S.; Kipp, Benjamin R.; Karnes, R. Jeffrey; Nassar, Aziza; Clayton, Amy C.; Henry, Michael R.; Sebo, Thomas J.; Zhang, Jun; Halling, Kevin C.
<x xml:space="preserve">Abstract</x> BACKGROUND The cytologic diagnosis of urothelial carcinoma (UC) of the upper urothelial tract (UT) is challenging. Using the UroVysion probe set adds diagnostic value for the detection of bladder cancer in voided urine. In instrumented UT specimens, the authors encountered positive UT cytology and fluorescence in situ hybridization (FISH) cases that did not demonstrate subsequent UT carcinoma. METHODS The performance of cytology and FISH in the presence or absence of concomitant bladder cancer within 2 years was compared in 61 patients (112 samples) from 2003 through 2009. The mean follow‐up was 3.2 years. The authors also compared the performance of near‐tetrasomy versus hypertetrasomy. Biopsy confirmation of UTUC in 21 patients was considered the gold standard. RESULTS Cytology alone was found to be poorly sensitive (38%) but highly specific (89%) for the detection of UTUC. FISH was found to increase the sensitivity of cytology and decrease specificity. Tetrasomy FISH resulted in many false‐positive cases. Other false‐positive FISH results were likely due to the presence of bladder cancer cells contaminating the UT specimen. CONCLUSIONS Caution should be used when evaluating instrumented urine specimens of the UT from patients with a previous history of bladder carcinoma, and tetrasomy FISH results should not be interpreted as abnormal because it significantly lowers the specificity of the test. The combination of cytology and FISH appears to have good specificity while maintaining good sensitivity in evaluating UTUC when using modified scoring criteria for the appropriate patient population. Cancer (Cancer Cytopathol) 2014;122:459–467. © 2014 American Cancer Society.